Bridging the generational gap: a study into lecturers’ and students’ classroom experiences - Idris, Nur Azimah; Mazeni, Noor Azizah; Libasin, Zuraira; Abdul Rahman, Mohd Syafiq (Unit Penerbitan JSKM, 2025)
This paper studies the generational gap between lecturers and students in higher education through narrative inquiry. In many universities, Generation X and Millennial lecturers teach classrooms filled predominantly with Generation Y students. These generational differences influence teaching and learning practices, communication styles, and approaches to technology. Rather than relying on quantitative measures, this study adopts a qualitative narrative approach to capture the lived experiences of both lecturers and students. Stories will be collected through interviews, focus group discussions, and reflective journals, allowing participants to describe their perspectives on classroom interactions. The analysis will identify themes such as technology as both a bridge and a barrier, tensions between authority and facilitation, and moments of connection and misconnection across generations. Findings show that while generational differences can create misunderstandings, they also open opportunities for deeper engagement and mutual learning. The study concludes that bridging generational gaps in higher education requires valuing diverse teaching identities, integrating technology thoughtfully, and fostering inclusive approaches that meet students’ evolving needs.